Ketimpangan Tersembunyi dalam Pelayanan Kesehatan Reproduksi Remaja Perempuan: Tinjauan Literatur Naratif - Marmi, Marmi; Nuryawati, Lina Siti; Antriana, Inna (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Adolescent-friendly reproductive health services have become a central priority in global and national health policies. However, utilization of these services by adolescent girls remains relatively low, even where programs and facilities are available. This condition indicates the presence of inequalities that are not fully captured by conventional indicators of service access. This article aims to critically examine scientific literature published over the past seven years that explores adolescent girls’ experiences in accessing reproductive health services, with a particular focus on hidden inequalities embedded in routine service practices. This study employed a narrative literature review approach, drawing on articles retrieved from Scopus, PubMed, SpringerLink, Google Scholar, and nationally accredited Indonesian journals. Eligible studies were analyzed thematically using a narrative synthesis framework. Eleven national and international articles were included, encompassing quantitative, qualitative, mixed-methods research, and systematic reviews. The findings indicate that inequalities in adolescent girls’ reproductive health services are multidimensional and often remain invisible in formal service assessments. Barriers extend beyond structural constraints, such as limited resources and geographic accessibility, to include individual, relational, and cultural factors. Social stigma, restrictive gender norms, concerns about confidentiality, and less empathetic communication with health care providers consistently shape adolescent girls’ decisions to delay, limit, or avoid service use. In addition, a persistent gap was identified between adolescent-friendly health policies and their implementation at the facility level. This review underscores the need for reproductive health services that are more experience-oriented, culturally responsive, and attentive to adolescents’ psychological safety to ensure meaningful access and utilization by adolescent girls.